Analysis-oriented models for FRP-confined concrete: 3D interpretation and general methodology. (1st August 2020) - Yang, Jia-Qi; Feng, Peng
Highlights: Geometrical interpretation of analysis-oriented models for FRP-confined concrete. Methodology for calibrating analysis-oriented models. Justification of design-oriented models. Abstract: An important application of fibre-reinforced polymer (FRP) composites in structural engineering is to confine concrete. In contrast to actively confined concrete, the stress-strain curve of FRP-confined concrete can have a second ascending branch when sufficient confinement is applied. Numerous analytical models have been proposed to predict the axial stress–strain behaviour of FRP-confined concrete. These models can be classified into two categories: (a) analysis-oriented models and (b) design-oriented models. In this paper, a 3-dimensional geometrical approach is proposed to interpret the general theory of analysis-oriented models based on three general equations. This approach provides an intuitive perspective to understand the analysis-oriented models and the mechanism of FRP-confined concrete. With this approach, a systematic methodology for calibrating analysis-oriented models is demonstrated, and the parameters in design-oriented models are justified. This methodology can also be applied to build analysis-oriented models for other concrete-type materials.